Internal Stakeholders' Claims on Branding a State University. Issue 4 (2nd October 2017) - Dholakia, Ruby Roy
ABSTRACT: Educational institutions, as part of the service sector, face unique challenges in developing and implementing an internal brand management (IBM) program. Internal stakeholders generally resist branding strategy. A case study of a public U.S. university describes the branding approach, which incorporated the multiple interests into an integrated strategy. The article contributes to our understanding of "doing branding" in the higher education sector and the unique role of IBM before, rather than after, a branding strategy has been developed.